2011
DOI: 10.1093/heapol/czr016
|View full text |Cite
|
Sign up to set email alerts
|

Meanings of blood, bleeding and blood donations in Pakistan: implications for national vs global safe blood supply policies

Abstract: Contemporary public policy, supported by international arbitrators of blood policy such as the World Health Organization and the International Federation of the Red Cross, asserts that the safest blood is that donated by voluntary, non-remunerated donors from low-risk groups of the population. These policies promote anonymous donation and discourage kin-based or replacement donation. However, there is reason to question whether these policies, based largely on Western research and beliefs, are the most appropr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
38
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 35 publications
0
38
1
1
Order By: Relevance
“…Recall the kidney operation, an 'available way for a marginal subject to imagine or to fear a different kind of future…through an operation that promises to turn one's organ into money' (Cohen 2011b, 136). We are thus reminded of the negative promise of South Asian tissue economies: the ways in which 'superstitions' are held to both block and structure them, their augmentation of the flow of dowries (Cohen 2001), rebooting of caste (Mumtaz et al 2012), and so on. Their rhetorical and actual futurial promise draws on and reentrenches features of pasts unconsigned to history.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recall the kidney operation, an 'available way for a marginal subject to imagine or to fear a different kind of future…through an operation that promises to turn one's organ into money' (Cohen 2011b, 136). We are thus reminded of the negative promise of South Asian tissue economies: the ways in which 'superstitions' are held to both block and structure them, their augmentation of the flow of dowries (Cohen 2001), rebooting of caste (Mumtaz et al 2012), and so on. Their rhetorical and actual futurial promise draws on and reentrenches features of pasts unconsigned to history.…”
Section: Resultsmentioning
confidence: 99%
“…Taking our cue from recent studies that have brought questions of the social implications of biotechnology strongly to the analytical fore and drawn attention to the variegated biopolitical milieus of South Asian tissue economies (Cohen 1999(Cohen , 2001(Cohen , 2004(Cohen , 2010(Cohen , 2011a(Cohen , 2011bBharadwaj 2000Bharadwaj , 2003Glasner 2009;Bharadwaj & Glasner 2009;Simpson 2004aSimpson , 2004bSimpson , 2009aSimpson , 2009bSimpson , 2011Sunder Rajan 2006;Reddy 2007;Egorova 2010, Mumtaz et al 2012, this special issue ranges widely -theoretically, thematically and regionally -in examining South Asian variants of and engagements with diverse modes of biological exchange: caste, gender and blood donation in Pakistan (Mumtaz & Levay), DNA testing amongst a former Untouchable community in south India (Egorova) and amongst diasporic Indians in Houston, Texas (Reddy), body (cadaveric) donation in India (De Looze), the use of fake blood in Bangladeshi cinema (Hoek), the mobilisation of blood, hearts and ketones to protest the Indian government's failure to provide redress or care to victims of the 1984 Bhopal industrial disaster (Banerjee), and blood-based political portraits and petitions in south India (Copeman). In considering this complex of issues we seek to extend the parameters of classic accounts of the role of substance transactions in the production of South Asian personhood into investigations of the biopolitics and economies of substance that shape people and communities in diverse parts of the subcontinent.…”
mentioning
confidence: 99%
“…The hurdles include lack of knowledge about the blood donation process, the financial constraints, the hassle involved, the family and cultural traditions and lack of interest of authorities. 12 Previously many national and international studies have been done on the general population regarding their views about voluntary blood donation. A number of studies have shown that females participation in blood donation process is low especially in the developing world.…”
Section: Attitudes and Beliefsmentioning
confidence: 99%
“…Similar thoughts were shared in the previous studies. 9,12 Others feared that they would not be able to carry their daily routine efficiently after blood donation. In majority of the cases the females were reluctant to donate blood without the permission of their male family members.…”
Section: Attitudes and Beliefsmentioning
confidence: 99%
See 1 more Smart Citation